Cementless Oxford unicompartmental knee replacement shows reduced radiolucency at one year. - Pandit, H; Jenkins, C; Beard, D; Gallagher, J; Price, A; Dodd, C; Goodfellow, J; Murray, D (2009)
We randomised 62 knees to receive either cemented or cementless versions of the Oxford unicompartmental knee replacement. The implants used in both arms of the study were similar, except that the cementless components were coated with porous titanium and hydroxyapatite. The tibial interfaces were studied with fluoroscopically-aligned radiographs. At one year there was no difference in clinical outcome between the two groups. Narrow radiolucent lines were seen at the bone-implant interfaces in 75% of cemented tibial components. These were partial in 43%, and complete in 32%. In the cementless implants, partial radiolucencies were seen in 7% and complete radiolucencies in none. These differences are statistically significant (p < 0.0001) and imply satisfactory bone ingrowth into the cementless implants.